Comparative anatomy of stem and leaf of Ricotia L. growing in Turkey - Selvi, Selami; Paksoy, Mehmet Yavuz (Bangladesh Journal of Botany, 2013)
The present paper deals with a comparative anatomy of stem and leaf of Ricotia species growing in Turkey. In addition, stomatal index and rate of these species were calculated. A diagnostic key based on combined stem, leaf and leaf epidermal characteristics were presented. The presence or absence of trichome, cortex parenchyma layer, sclerenchyma, mesophyll structure and epidermal surface were found to be important characters for the identification of Ricotia species. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15875 Bangladesh J. Bot. 42(1): 123-130, 2013 (June)